Altered Immune Responses in Mice After Receiving Nicotine-pulsed Mesenchymal Stem Cell-conditioned Medium - Mahmoudzadeh, Leila; Abtahi Froushani, Seyyed Meysam; Hobbenaghi , Rahim; Mahmoudian , Alireza; Mohammadi , Vahid (Archives of Advances in Biosciences, 2021)
Introduction: Previous investigations have documented that nicotine-pulsed mesenchymal stem cells (MSCs) can induce an anti-inflammatory phenotype in some immune cells in vitro. This study aimed to assess the effects of nicotine-pulsed MSCS in the function of immune cells, macrophages, and lymphocytes of mice receiving these cels. Materials and Methods: Bone marrow-derived MSCs (1.5×106) were seeded in a T75flask and incubated with 0, .1, .5, or 1 μM nicotine until the cells reached 90% confluency. Afterwards, immunophenotyping change, vitality, concentration of TGF-β, IL-10, and IDO levels of the MSC-conditioned medium were examined. Correspondent to in vitro results, the C57BL/6 mice intravenously received 400 μL of the conditioned medium of MSCs (CM), conditioned medium of nicotine (.5 μM)-pulsed MSCs (CMN), or medium. After 12 h, the lymphocytes, neutrophils, and peritoneal macrophages of the mice were isolated and their function was evaluated ex vivo. Results: The least effective dose concentration of nicotine that led to an anti-inflammatory environment by the MSC-conditioned medium was 0.5 μM. Nicotine at this concentration prompted a higher level of TGF-β, IDO concentration in the conditioned medium. However, this concentration did not affect the MScs’ markers expressions or MScs’ vitality. T lymphocytes isolated from the mice receiving CMN showed a significant decrease in proliferation rate. The ratio of the IFN-γ gene expression to IL-4 gene expression in splenocytes was significantly reduced in the mice receiving CMN compared to the mice receiving CM. The neutral red uptake, respiratory burst, and nitric oxide production of the peritoneal macrophage only decreased in the mice treated with CMN. These factors also decreased in neutrophils isolated from mice receiving CM or CMN. However, these decreases were more prominent in the mice treated with CMN. Conclusion: Treatment of MSCs by nicotine may be a promising strategy to enhance the immunomodulatory properties of these cells.